Management of severe Raynaud’s Phenomenon secondary to autoimmune vasculopathy in a young woman - Amissah-Arthur, M.; Wu, L.P. (Ghana Med J, 2021)
Raynaud’s phenomenon as a cause of acute limb ischaemia in the warmer climates of Sub-Saharan Africa region is uncommon because it is usually thought of as a disease common in cold weather. The prevalence of connective tissue diseases among Black Africans is increasing, and these conditions are associated with secondary Raynaud’s phenom enon and ischaemic digital lesions. We present the case of a 36-year old female with dermatomyositis/systemic scle rosis overlap and secondary Raynaud’s phenomenon who presented with acute limb ischemia (wet gangrene of all digits) in a Tertiary Hospital in Ghana. Young patients presenting with acute limb ischaemia should also be screened for an underlying connective tissue disease. In patients with connective tissue disease, the onset of digital vasculopathy can be rapid and progressive, hence treatment must be prompt and comprehensive to enable better clinical outcomes.
Research Article
Keywords: Acute limb ischaemia; autoimmune; connective tissue disease; secondary Raynaud’s phenomenon; digital vasculopathy